Estudio sobre la relación entre participación laboral femenina y la probabilidad de ser víctima de violencia doméstica en el Perú 2009- 2019 - Andía Vera, Claudia Lucia Fátima (2021)
It is evident that the female gender has been entering the paid work environment and positioning itself more in it. In addition, domestic violence against women in Peru develops within an existing gender gap that is more evident, by a society that is not very inclusive in norms, laws and rights and at the cultural level, configuring it as a society where opportunities for men predominate. There are many cases of domestic violence reported by ENDES, and the CEM at the national level. The main objective of this research is to determine through the approach of a Logit econometric model that allows to measure, by means of dummy variables, the probability of occurrence conditioned to a specific situation that a Peruvian woman between 18 and 59 years old is a victim of some type of violence Domestic is greater when it is used, the methodology used was of an empirical and critical evolutionary temporal scope, of a correlational and explanatory type of non-experimental design. The sample is made up of 1,067 Peruvian women between 18 and 59 years of age from the different regions of the country, the distribution of interviews was based on the percentage of occurrence of cases detailed in the CEM reports, and the instrument used was a directed survey, which sought answer the hypothesis. The results concluded that there is a probability of 32.21% that a working woman between 10 and 59 years old is a victim of domestic violence by her partner, demonstrating a positive relationship between the proposed variables. For the levels of violence according to their classification, the model calculations determined a probability of 10.05% that the woman is a victim of patrimonial violence, a 9.25% probability that she is a victim of psychological violence, 6.29% of being a victim of physical violence and finally 6.61 % probability of being a victim of sexual violence.